Elective Lung Resections in the Elderly: Where Do We Draw the Line? - Smelt, Jeremy; Lovejoy, Christopher A.; Thakker, Rudrik; Hunt, Ian; Martin, Fionna; Tan, Carol (The Thoracic and Cardiovascular Surgeon, 2020)
Introduction The increasing longevity of the Western population means patients with a more advanced age are being diagnosed with resectable disease. With improvements in imaging and diagnostic capabilities, this trend is likely to develop further. As a unit operating on a higher proportion of older patients and with limited literature regarding the population of older than 85 years, we retrospectively compared the outcomes of patients older than 85 years in our unit treated with elective lung resection for non-small cell lung cancer (NSCLC) with those between the age of 80 and 84 years inclusive.Methods All patients who underwent elective lung cancer resection between the years 2012 and 2015 were identified from the National Thoracic Surgical Database.Results A total of 701 elective lung resections were performed during this time frame; 76 patients between the ages of 80 and 84 years and 18 patients older than 85 years. The follow-up period was 3 to 7 years. There was a significant increase in the Thoracic Surgery Scoring System (2.04; 2.96%, p = 0.0015) and a significant reduction in the transfer factor (94.7; 69.5%, p = 0.0001) between the younger and older groups. There were three (3.9%) in-hospital deaths in the 80 to 84 years age group and no in-hospital deaths in the 85 years and older age group.Conclusion This study demonstrates that surgery for early NSCLC can be safely performed in 85 years and older population. This is a higher risk population and parenchymal-sparing procedures should be considered.
Keywords: geriatric services; thoracic surgery; in-hospital mortality; lung cancer